Comparative evaluation of root canal morphology in mandibular first premolars with deep radicular grooves using direct vision, dental operating microscope, 2D radiographic visualisation and micro-computed tomography - Mohmed Isaqali Karobari; Hany Mohamed Aly Ahmed; Mohd Fadhli Bin Khamis; Norliza Ibrahim; Tahir Yusuf Noorani (PLoS ONE, 2025)
Objectives The objective of this study was to evaluate the effectiveness of clinically applicable diagnostic methods such as Direct Vision (DV), Dental Operating Microscope (DOM), and two-dimensional (2D) radiographs in detecting canal orifices and root canal configurations in mandibular first premolars with deep radicular grooves. The study also aimed to compare these methods with micro-computed tomography (micro-CT) to better understand their diagnostic capabilities and to assess the applicability of the Ahmed et al. (2017) classification system across different imaging modalities. Methods A total of 133 mandibular first premolars with deep radicular grooves were scanned using micro-CT. After scanning, two examiners, blinded to micro-CT results, accessed and examined the root canal orifices of the study samples under DV, and DOM. Further evaluation of the root canal configurations was undertaken using exploration and 2D radiographic images. A second round of relocation of canals was undertaken if the radiographic view showed the presence of a missed canal. The data were then compared with the original reconstructed micro-CT images. Descriptive statistical analysis, Kappa and chi-square tests were performed to compare between methods and examiners, and the p-value was set at 0.05. Results Except for three teeth, all samples exhibited multiple canals. Micro-CT data revealed a wide range of root canal configurations, with the most common being 1MFP1-2 (19.54%), followed by 1MFP1-2-3 (15.78%), 1MFP1-2-3-2 (5.26%), and both 1MFP1-2-4 and 1MFP1-2-1 configurations, each at 4.51%. For both examiners, using the DOM resulted in detection of more canal orifices compared to DV (p < 0.001). A number of root canal configuration types including 1MFP1-2 and 1MFP1-2-1 was identified using exploration and radiographic imaging. Both examiners identified additional canals in the relocation phase. A significant difference was found when the radiographic method is compared with micro-CT results (p < 0.001), in which the latter method showed more complex root canal configuration types. Conclusions Mandibular first premolars with deep proximal grooves exhibit considerable variability and complexity in their root canal systems. The use of a dental operating microscope (DOM) significantly improves the detection of canal orifices compared to direct vision. The most frequently observed root canal configuration was 1MFP1-2. A high percentage of additional canals may be missed due to atypical locations of bifurcations along the root. While micro-CT imaging is not applicable in clinical settings, it remains a valuable reference tool in studies for enhancing our understanding of root canal morphology and guiding the development of clinically feasible diagnostic strategies.